Lingwodydaktyczny potencjał ChatGPT w nauczaniu języków obcych - Iakovleva, Olga (Neofilolog, 2024)
ChatGPT can be used as an alternative resource when learning a foreign language. It has a wide range of applications, such as: working with vocabulary and grammar, practicing, testing and proofreading texts, practicing speaking, creating learning materials, automatically translating texts and providing information about countries, cultures, history and other aspects related to the foreign language being taught. Phraseological competence is an important element of general communicative skills, which enables the learner of a foreign language to use the language correctly, freely, and broadens knowledge of intercultural issues. The article analyses the possibilities of using a chatbot when learning foreign language phraseology. The study aims to assess the effectiveness of ChatGPT in the process of foreign-language phraseology acquisition. Texts from Russian and Polish textbooks containing phraseological units are used as material. The results reveal that for this purpose ChatGPT can be used partially because its effectiveness is related to the type of specific task. The Chatbot gives worse results when it is tasked with translating phraseological compounds or citing an example of their use, while it is promising as an alternative resource for creating educational content.